Dissecting Motor Neuron Disease With Drosophila melanogaster - Walters, Rachel; Manion, John; Neely, G. Gregory (Frontiers in Neuroscience, 2019)
Motor Neuron Disease (MND) typically affects patients during the later stages of life, and thus, MND is having an increasingly devastating impact on diagnosed individuals, their families and society. The umbrella term MND refers to diseases which cause the progressive loss of upper and/or lower motor neurons and a subsequent decrease in motor ability such as amyotrophic lateral sclerosis (ALS) and spinal muscular atrophy (SMA). The study of these diseases is complex and has recently involved the use of genome-wide association studies (GWAS). However, in the case of MND, it has been difficult to identify the complex genetics involved in subtypes, and functional investigation of new candidate disease genes is warranted. Drosophila is a powerful model for addressing these complex diseases. The UAS-Gal4 system allows for the upregulation of Drosophila genes, the ‘knock-down’ of genes and the ectopic expression of human genes or mutations in a tissue-specific manner; often resulting in Drosophila fly lines which exhibit typical MND disease pathologies. These can then be further interrogated to identify disease-modifying genes or mutations and disease pathways. This review will discuss both of the common MNDs and the current Drosophila models which are being used to research the genetic basis and different pathologies of MND.